Hydatid Cyst of the Adrenal Gland: A Clinical Study of Six Cases - Ali Horchani; Yassine Nouira; Kais Nouira; Haikel Bedioui; Emna Menif; Zoubeir Ben Safta (The Scientific World Journal)
Hydatid cyst of the adrenal gland (HCAG) is an exceptional occurrence. We report our experience of six cases of HCAG and discuss the diagnosis and treatment of this hydatid localization. We retrospectively reviewed and analyzed the clinical files of six patients admitted to our institution from January 1990 to December 2000 for HCAG. Patients varied in age from 24—59 years. They were five males and one female. One patient had a history of pulmonary hydatidosis treated surgically 10 years previously. Five patients presented with lumbar pain and one patient had bouts of hypertension, headache, and palpitation. Physical examination was normal except in one patient who was hypertensive. Preoperative diagnosis was highly suggested by ultrasonography. CT scan performed in all cases clearly showed the relationship of the cyst with adjacent organs. Serology tests were positive in two cases. One patient had elevated urine VMA and was operated on with the diagnosis of cystic phaeochromocytoma. All six patients were operated on and had either an adrenalectomy (two cases) or partial pericystectomy (four cases). In one case, partial pericystectomy was conducted through a retroperitoneal laparoscopic approach. The hydatid nature of the cyst was confirmed pathologically. All patients had a smooth postoperative course with no cystic recurrence on follow-up. The diagnosis of HCAG is based mainly on ultrasonography and CT scan. Surgery with either partial or total excision of the cyst, with or without preservation of the adrenal gland, is the treatment of choice.